2011
DOI: 10.1063/1.3554422
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the spin polarization of excitons in a single quantum dot by optical means

Abstract: Circular polarization studies of photoluminescence from the neutral (X0) and the positively charged (X+) excitons are reported for individual InAs/GaAs quantum dots (QDs). High polarization degrees, 60% for X0 and 73% for X+, were recorded without any external magnetic field applied. These studies show that the QD polarization and population dynamics are controllable either by varying the photoexcitation intensity or by using a second IR laser excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In contrast to those studies performed under large external magnetic fields, experimental reports under zero magnetic field have so far been insufficient [25][26][27][28][29] . As shown later, excitation by a circularly polarized beam induces a considerable Overhauser field under a wide range of experimental conditions, even if one does not intend to induce an Overhauser field.…”
Section: Introductionmentioning
confidence: 82%
“…In contrast to those studies performed under large external magnetic fields, experimental reports under zero magnetic field have so far been insufficient [25][26][27][28][29] . As shown later, excitation by a circularly polarized beam induces a considerable Overhauser field under a wide range of experimental conditions, even if one does not intend to induce an Overhauser field.…”
Section: Introductionmentioning
confidence: 82%
“…Ingenious and numerous experimental studies have shown the influence of reduction of dimensionality on band structure then on the emission-absorption energies as well as on excitonic transport mechanisms in quantum wells heterostructures [11]. Others determined the intersubband transitions within semiconductor quantum dots (QDs) [12,13] if not manipulating the excitonic spin states [14,15]. In this, context, a new class of nanoparticles recently appeared, the core/shell quantum dots (CSQDs) such as ZnS/ZnO or CdSe/ZnTe.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, no circularly polarized emission should be observed when no external magnetic field is applied. However, it was recently shown that this restriction can be relaxed and PL from X 0 can become partially circularly polarized [24,25] when an effective magnetic field (i.e. Overhauser field) is created via dynamic polarization of nuclear spins of lattice atoms within QDs under cw excitation by circularly polarized light.…”
Section: Origin Of the Qd Pl And Pl Polarizationmentioning
confidence: 99%